PRAGMATIC ASPECTS OF POLITICAL COMMUNICATION (TAMADDUN NURI JURNALI, 2024)
In this article, we will analyze the communication process in terms of information transfer, interaction, mutual perception, deixis, linguistic units, meaning, function, pragmatics, and movement of linguistic signs in speech.